Madagascar Economic Update, Spring 2019 : Managing Fuel Pricing - World Bank (World Bank, Washington, DC, 2019)
Welcome to the Spring 2019 edition of the World Bank's Madagascar Economic Update, which presents recent economic developments and our medium-term outlook. The economy has continued to perform well, with growth in 2018 estimated at 5.2 percent, above regional and global averages. External demand for Malagasy goods and services remains strong, with exports such as cash crops, metals and business process outsourcing performing well. A small but dynamic private sector is responding to this increased economic activity with banking, logistics and services to support companies all under expansion. This edition of economic update focuses on managing fuel pricing.